2021
DOI: 10.3233/bmr-200325
|View full text |Cite
|
Sign up to set email alerts
|

Are there any changes in strength after the application of Kinesio taping in lateral epicondylalgia?

Abstract: BACKGROUND: In 1973, Dr. Kenzo Kase developed Kinesio taping from the hypothesis that this external component could aid the functions of muscles and other tissues. There are different studies on this issue, but none has completely clarified the research question. OBJECTIVE: To study the application of Kinesio taping in the variation of isometric muscle strength of the hand extension and grip, isokinetic strength of the pronation and supination movements, and the time it takes to reach that strength in patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Two researchers then examined the full texts of the 26 chosen studies. Included in this review were 11 RCTs [ 17 , 19 , 21 , 22 , [26] , [27] , [28] , [29] , [30] , [31] , [32] ] and the reporting bias was deemed to be low for all of them ( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two researchers then examined the full texts of the 26 chosen studies. Included in this review were 11 RCTs [ 17 , 19 , 21 , 22 , [26] , [27] , [28] , [29] , [30] , [31] , [32] ] and the reporting bias was deemed to be low for all of them ( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In LET cases, controversies regarding the efficacy of KT persist. Some randomized controlled trials indicated that KT was effective for decreasing pain intensity, recovering grip strength, and improving functionality in patients with LET [ [15] , [16] , [17] ]; while other studies demonstrated that the application of KT produced no effects on muscle strength and KT exerted an effect similar to that of a placebo [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation